Grazing land parcels in villages with land use plannig in Chalinze District Council, Coast Region - Kalenzi, Deus (International Livestock Research Institute, 2018)
Map showing grazing land parcels allocated in village land use plans in Chalinze District, Coastal (Pwani) region, Tanzania in 2018.